China-ASEAN relations and international law - Zou, Keyuan (Chandos Asian studies series., 2009)
Our contemporary era has witnessed the remarkable development of China-ASEAN relations. Both sides have pledged to establish and develop a comprehensive cooperation. However, any development of international relations is governed by international legal principles, norms and rules, such as the Charter of the United Nations and general international law. There is no exception for China-ASEAN relations. The book discusses and explains China-ASEAN relations from an international law perspective and covers a wide range of legal topics and legal issues. The first book which attempts to discuss and explain China-ASEAN relations in an international law perspectiveCovers a wide range of legal topics and issues significantly existing in the development of China-ASEAN relationsUnique in the sense that it specifically deals with the relationship between one country and one international/regional organization.